Research on routing scheduling technology of computing power network - Ran PANG; Xinxin YI; Liang XIN; Chang CAO; Xiongyan TANG (Dianxin kexue)
With the needs of high-quality development of the digital economy, the research on computing power network is accelerating.How to realize the integrated scheduling of computing resources and network resources becomes the primary challenge for computing power network.The evolution of computing power network was introduced, the resource awaring and routing scheduling technology of computing power network were analyzed, and a hybrid routing scheduling solution for computing power network was proposed to realize the ability of flexible on-demand, fast routing and easy implementation.The implementation process of the hybrid routing scheduling solution in the remote driving scenario of the Internet of vehicles was introduced, which supported the provision of differentiated services integrating computing and networking and fast tuning when the vehicle was moving.